Optimal orthogonal designs in two blocks based on F-squares for mixture inverse model in four components. (2015) - Husain, Bushra; Sharma, Sanghmitra
Orthogonal block designs for Scheffés quadratic model in three and four components have been considered by John (1984), Czitrom (1988, 1989), Draper et al. (1993), Chan and Sandhu (1999), and Ghosh and Liu (1999). Singh (2003) considered optimal orthogonal designs in two blocks for Darroch and Waller's quadratic mixture model in three and four components. Aggarwal et al. (2009) have studied mixture designs in orthogonal blocks using F-squares. A mixtures model with inverse terms was presented by Draper and St. John (1977). In this paper, we have constructed optimal orthogonal designs in two blocks based on F-squares for a mixture inverse model in four components with two component proportions at the same level. Conditions required for orthogonality are also given.